University Strategy and Implementation Using the David Strategic-Management Model: A Case Study from Indonesia - Kho, Ardi; Rumanti, Elisabeth Dewi; Sudibjo, Niko; Nanda, Kezia Arya (Universitas Pelita Harapan, 2021)
The competency standards of university graduates must comply with the National Standards of Education, the Indonesian National Qualification Framework (KKNI), and other criteria set by the university. Universities need to set strategies and implementations to achieve the standard of graduate competence consisting of attitudes, knowledge, and skills stated in the formulation of graduate learning achievements. A case study using a qualitative approach was conducted at the university in Banten, Indonesia. The purpose of this study is to explore academic strategies in university. This includes examining the key drivers for strategic planning, the opportunities pursued in strategic planning, and challenges encountered in the process of strategic planning. The findings suggest that key drivers for strategic planning in the university include market competition and customer requirements. Secondly, the findings are the university should pursue three major strategic planning opportunities, including improved academic operational efficiency, improved student competency, and lecturer’s qualification, as well as improved services of the university. Thirdly, the change management process is reactive and not necessarily transformational in its degree, even though it can involve large-scale changes. The findings integrated into a model contribute to understanding the relationship between the context of strategic planning, the content of strategic planning, and the process of strategic planning in university.